The burden of infectious diseases in the Brazilian Southern state of Santa Catarina. Issue 2 (March 2016) - Traebert, Jefferson; Nickel, Daniela A.; Traebert, Eliane; Escalante, Juan J.C.; Schneider, Ione J.C.
Summary: Infectious diseases are still significant causes of deaths in Brazil. The objective of this study was to estimate the burden of selected infectious diseases in the Brazilian Southern state of Santa Catarina in 2011. An ecological study was conducted. The infectious diseases included were HIV/AIDS, tuberculosis, hepatitis B, hepatitis C, Chagas disease, diarrheal diseases and other infectious diseases. Data were collected from official health information systems. Disability Adjusted Life Years (DALY) were estimated by the sum of Years of Life Lost (YLL) and Years Lived with Disability (YLD). 45, 237.33 DALYs were estimated, with a rate of 685.46 DALYs per 100, 000 population. 92.9% was due to YLL and 7.1% to YLD. Men and the age range of 0–4 years presented higher burden. The highest burden was attributed to HIV/AIDS. There was a high concentration of burden rates in the coast regions of the state. It could be concluded that more than 90% of the burden was attributed to the early mortality component. The highest burden was observed among men, children under 5 years of age and at the coast regions of the state. The highest levels of burden were due to HIV/AIDS.